TEKNIK PEMINJAMAN KANAL DENGAN METODE BDCL ((BORROWING WITH DIRECTIONAL CHANNEL-LOCKING) PADA SISTEM KOMUNIKASI SELULER - Ajub Ajulian Zahra M (Diponegoro University, 2007)
The cellular mobile mobile telephone system has found important applications in metropolitant areas. Its different types of channel assignment schemes has been adopted in many cellular systems. To satisfy the high demand of mobile telephone service channel needs to be reused in different noninterfering cells. In the fixed assignment strategy, a set of nominal channels is permanently assigned to each cells, and the same set of channels is reused some distance away. That distance is called the cochannel reuse distance. Using the fixed channel assignment strategy, an arriving call can only be served by the nominally assigned channels. If all nominal channels are assigned, new calls are blocked. Borrowing channel assignment (BCA) is the simplest allocation scheme. In borrowing channel assignment, channel assignment is initially fixed that is a channel set is preassigned to each cell. If there are incoming calls to a cell whose channels are all occupied, the cell borrows channels from its neighboring cells under the constraint of no interference. When a channel is borrowed, several other cells are not allowed to use that channel. In this final project two channel assignment strategies are proposed. They are the borrowing with directional channel-locking and the fixed channel assignment. BDCL performance is compared with fixed channel assignment (FCA). In this borrowing with directional channel-locking (BDCL), when a channel is borrowed, the locking of this channel in the cochannel is restricted only those affected by this borrowing.. In this final project the simulated cellular systems contains 49 hexagonal cells all cells with eight nominal channel. The simulation shows that with the newly proposed BDCL strategy can give a lower lower blocking probability than FCA under nonuniform traffic distribution.